The long way to tax transparency: lessons from the early publishers of country-by-country reports - Sarah Godar; Giulia Aliprandi; Tommaso Faccio; Petr Janský; Katia Toledo Ruiz (International Tax and Public Finance, 2024)
In this paper, we analyse a sample of voluntarily published country-by-country reports (CbCRs) of 35 multinational enterprises (MNEs). We assess the value added and the limitations of qualitative and quantitative information provided in the reports based on a comparison to individual MNEs' annual financial reports and aggregate CbCR data provided by the OECD. In terms of data quality, we find that the inclusion of intra-company dividends and equity-accounted profits are a minor concern on average but that for individual MNEs corrections might be substantial. Our sample MNEs seem to pay higher effective tax rates than the global average and many of them report relatively little profit in tax havens. We only find a very weak correlation of the location of profits and effective tax rates. This might indicate that more tax transparent MNEs avoid taxes less aggressively. However, our assessment of different tax risk indicators reveals important variations between companies.
Keywords: F23; H25; H26; 340; Multinational corporation; Country-by-country reporting; Effective tax rate; Profit shifting; Tax haven